PENGARUH MOTIVASI KERJA INTRINSIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. KERETA API INDONESIA (PERSERO) DIVISI REGIONAL II SUMATERA BARAT - Aminar Sutra Dewi; Putri Wulandari (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The purpose of this study was to examine the effect of intrinsic work motivation and work discipline variables on employee performance at PT. Kereta Api Indonesia (Persero) Regional Division II West Sumatra. Collecting data through questionnaires to 98 respondents using saturated sampling technique, where all members of the population are sampled, using multiple linear regression testing with the help of the SPSS application. The results of the study show that intrinsic work motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance